The synergy of debt management, big data technology and corporate decision-making: A catalyst for enhanced financial performance through operational efficiency and sustainable business strategies - Sonjaya, Yaya; Agustia, Dian; Sabaruddin, La Ode (International Journal of Innovative Research and Scientific Studies, 2024)
This research explores the impact of debt management and big data technology utilization in management decision-making on corporate financial performance with a focus on operational efficiency and sustainable business strategy effectiveness as intervening variables. It aims to delve into how a firm's debt management strategies and its incorporation of big data into decision-making processes influence its financial outcomes. This study scrutinizes the company's approach to managing its debt structure and levels while the use of big data technology in decision-making reflects the integration of advanced technology in strategic planning by examining debt management. The study further investigates how operational efficiency and the effectiveness of sustainable business strategies act as intermediaries in this relationship indicating the role of a firm's internal processes and corporate strategy in driving financial success. Moreover, the research considers mediating variables such as industry type and market competition level which could affect the relationship between the independent and dependent variables. This study aims to test these relationships providing insights into the influence of debt management and big data technology on financial performance using statistical data analysis. Expected outcomes include a deeper understanding of the strategic implications of these factors for achieving sustainable and improved financial performance in a complex business landscape. Emphasizing the importance of efficient debt management and the strategic application of big data technology, the study highlights the necessity for firms to adopt wise financial resource management and innovative decision-making approaches to navigate the challenges of the modern business environment effectively.